The Relationship Between Maternal Clean and Healthy Living Behavior (PHBS) and The Incidence of Diarrhea in Toddlers - Aghani, Fandi Nur; Zuhroh, Diah Fauzia; Suminar, Ervi (Universitas Muhammadiyah Gresik, 2024)
Diarrhea is a condition with symptoms by frequent of bowel movements with liquid consistency. Diarrhea in children often occur due to poor of personal and environmental hygiene. A person’s behavior is one of the main factors that determine the level of health. This research aims to analyse the relationship between mother’s clean and healthy lifestyle beahior with the incidence of diarrhea in toddlers. This research used cross sectional approach with a population of 157 mothers who were sick in the children's room at the Muhammadiyah Hospital Gresik. Sampling was carried out in a total sampling. using a questionnaire. Collected of data use questionnaire was distributed to respondents. The results showed most of them did not experience diarrhea in toddlers as much as 81 (52%) and most of them had positive behavior as many as 82 (52%). The results of the analysis were obtained using the Chi-Square test where P = 0.000 is less than 0.05, so H0 is rejected, which means that there is a relationship between the mother's clean and healthy lifestyle and the incidence of diarrhea in toddlers